1996
DOI: 10.1136/jech.50.1.94
|View full text |Cite
|
Sign up to set email alerts
|

Is the short form 36 (SF-36) suitable for routine health outcomes assessment in health care for older people? Evidence from preliminary work in community based health services in England.

Abstract: Study objective -To examine the short form 36 (SF-36) health status measure when used to assess older people's views ofthe outcome ofcommunity based health care. Design -Completion of a structured questionnaire, before and after intervention alongside in-depth interviews with a subsample of the interviewees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 16 publications
2
33
1
Order By: Relevance
“…Several studies have reported a limited effect of exercise on HRQOL in relatively healthy older adults [5,6] . Moreover, although the SF-36 is still the most frequently used HRQOL measure, several studies demonstrated that the SF-36 is limited by ceiling effects and thus may be insensitive to clinically relative changes in HRQOL in healthy elderly subjects [8,[27][28][29][30][31] . In the present study, the baseline scores of the participants in the function group and the control group were in the 50th and 75th percentile of US norm scores for women aged 65 and older [21] and above Dutch norm scores, indicating that the participants were in excellent physical and MH.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported a limited effect of exercise on HRQOL in relatively healthy older adults [5,6] . Moreover, although the SF-36 is still the most frequently used HRQOL measure, several studies demonstrated that the SF-36 is limited by ceiling effects and thus may be insensitive to clinically relative changes in HRQOL in healthy elderly subjects [8,[27][28][29][30][31] . In the present study, the baseline scores of the participants in the function group and the control group were in the 50th and 75th percentile of US norm scores for women aged 65 and older [21] and above Dutch norm scores, indicating that the participants were in excellent physical and MH.…”
Section: Discussionmentioning
confidence: 99%
“…In order to understand the dynamics of the survey findings at the individual level we develop an argument which has similarly been developed by Hill et al (1996) MacIntyre et al (1993) concerning the need to accumulate empirical information about peopleʼs experiences in different areas.…”
Section: 8mentioning
confidence: 99%
“…The concept of need used in this study can be considered to encompass both met and unmet need in terms of functional status (which takes into account the limitations described by Hill et al (1996)). Through in-depth interviews, using these key themes as guidance, the findings from the SF-36 can be compared with the findings from the qualitative study.…”
Section: 10mentioning
confidence: 99%
“…Convergent validity with unidimensional instruments was found for the HSQuale General Outlook, Physical Functioning, and Emotional Well-Being domains. The skewed frequency distribution of patient scores found for the Pfeiffer Short Portable Mental Status Questionnaire (Ͼ90% of subjects scored perfectly) and the Duke-UNC Functional Social Support Questionnaire (nearly 50% of subjects scored Ն38 of 40 points) imply these instruments are inappropriate for 55,56 and it may account for some of the overlapping strong correlations. Construct validity of the OSQ was established by showing appropriate discriminant validity.…”
Section: Discussionmentioning
confidence: 99%